Job Shop Material Control Based on the Principles of Quick Response Manufacturing - Bong, C.S.; Chong, K.E.; How, W.C. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Today cutting-edge companies will capitalize on time as a key driver of competitive advantage. Although the Paired-cell Overlapping Loops of Cards with Authorization (POLCA) of Quick Response Manufacturing (QRM) is universally adopted as a material control mechanism in the shop floor, this paper is exploring its other principle. The newly thought approach, Utilization Based (UB) system is driving a whole new ways of controlling material flow in the production with the emphasis on operate the factory at optimum machine utilization. A simulation study was conducted to compare the POLCA and UB system. The deterministic metrics such as Manufacturing Critical-path Time (MCT), Throughputs (TP), Work in Progress (WIP) show that UB system is a viable alternative especially in the job shop environment with process layout. However, this method involves subcontracting in order to maximize output and minimize waiting time. The simulation study fulfilled the objectives of evaluating two different systems using the same set of inputs. The related performance measures prove the UB approach is as feasible as POLCA adopted in the job shop environment with some outperforming results.